2015
DOI: 10.4238/2015.april.30.6
|View full text |Cite
|
Sign up to set email alerts
|

Relation between prognosis and changes of MBP and S100B in premature infants with periventricular leukomalacia

Abstract: ABSTRACT. This study aims to explore the relation between changes in myelin basic protein (MBP) and S100 protein (S100B) serum levels and prognosis in premature infants with periventricular leukomalacia (PVL). In our hospital, 78 premature infants with PVL and 43 normal premature infants were studied from July 1, 2007 to December 31, 2008. MBP and S100B serum levels were detected at 1, 3, 7, and 14 days after birth by using enzyme-linked immunosorbent assay. All infants were followed four times (once every 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…In accordance with our study, in most previous studies S100B levels in preterm controls were stable over time, whereas levels in preterms with encephalopathy were decreasing over time ( 74 , 76 , 78 , 79 ). On the contrary, there were reports of cases of severe asphyxia ( 79 ) or PVL where S100B levels presented an increasing trend over time ( 74 , 78 ). S100B has a very small half-life of 30–100 min ( 8 ) and thus protracted increased levels depict protracted cell necrosis or apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with our study, in most previous studies S100B levels in preterm controls were stable over time, whereas levels in preterms with encephalopathy were decreasing over time ( 74 , 76 , 78 , 79 ). On the contrary, there were reports of cases of severe asphyxia ( 79 ) or PVL where S100B levels presented an increasing trend over time ( 74 , 78 ). S100B has a very small half-life of 30–100 min ( 8 ) and thus protracted increased levels depict protracted cell necrosis or apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…An increase of S100B in prematures with encephalopathy was observed on the first day of life compared to preterms without detectable brain damage, a constant observation in previous studies ( 74 78 ). In accordance with our study, in most previous studies S100B levels in preterm controls were stable over time, whereas levels in preterms with encephalopathy were decreasing over time ( 74 , 76 , 78 , 79 ). On the contrary, there were reports of cases of severe asphyxia ( 79 ) or PVL where S100B levels presented an increasing trend over time ( 74 , 78 ).…”
Section: Discussionsupporting
confidence: 75%
“…Another study done by Huang et al [9] on 121 preterm neonates with GA<34 weeks and were classified into normal group (without PVL)and abnormal group (with PVL) according to head U/S resulted in S100B levels of PVL infants were significantly increased at 1, 3, and 7 days, and were highest on the 7th day. There was a significant difference between the normal group and the PVL group.…”
Section: Discussionmentioning
confidence: 99%
“…"Studies in different biological fluids, have demonstrated adequate effectiveness in predicting adverse neonatal outcomes or NBI. Yet, there is still no consent on which biological fluid or method (one sample or multiple longitudinal sampling) is the most effective for the early detection of premature neonates at high risk to develop NBI when using S100B as a predictor" [9]. "Although S100B protein will come from other organs, that is, muscle, heart, fractured bone, and adipose tissue, extracerebral sources of S100B do not contribute to the increase in serum concentrations Hence, serum S100B protein is considered a specific protein of brain damage.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are also consistent with the observation that neither neonates that died (n=5) nor those with II-IV grade IVH showed significantly higher GFAP concentrations when compared to neonates of either the control or case group during the first 3 days of life (results not shown). Although the levels of GFAP were more elevated in these neonates when compared to controls, it seems that GFAP is either of limited value in the prognosis of NBI in the general population of premature neonates or not as powerful as other biomarkers, such as S100B [ 37 , 38 ]. The latter is considered as one of the most effective biomarkers to predict severe types of NBI in premature neonates according to a number of previous studies, including ours [ 13 ].…”
Section: Discussionmentioning
confidence: 99%